In Vivo Visualization of Active Polysynaptic Circuits With Longitudinal Manganese-Enhanced MRI (MEMRI) - Almeida-Corrêa, Suellen; Czisch, Michael; Wotjak, Carsten T. (Frontiers in Neural Circuits, 2018)
Manganese-enhanced magnetic resonance imaging (MEMRI) is a powerful tool for in vivo non-invasive whole-brain mapping of neuronal activity. Mn2+ enters active neurons via voltage-gated calcium channels and increases local contrast in T1-weighted images. Given the property of Mn2+ of axonal transport, this technique can also be used for tract tracing after local administration of the contrast agent. However, MEMRI is still not widely employed in basic research due to the lack of a complete description of the Mn2+ dynamics in the brain. Here, we sought to investigate how the activity state of neurons modulates interneuronal Mn2+ transport. To this end, we injected mice with low dose MnCl2 (i.p., repeatedly for 8 days) followed by two MEMRI scans at an interval of one week without further MnCl2 injections. We assessed changes in T1 contrast intensity before (scan 1) and after (scan 2) partial sensory deprivation (unilateral whisker trimming), while keeping the animals in a sensory enriched environment. Whole brain analysis revealed a single cluster with higher signal in scan 1 compared to scan 2: the left barrel cortex corresponding to the right untrimmed whiskers. In the inverse contrast (scan 2 > scan 1), a number of brain structures, including many efferents of the left barrel cortex were observed. These results suggest that continuous neuronal activity elicited by ongoing sensory stimulation accelerates Mn2+ transport from the uptake site to its projection terminals, while the blockage of sensory-input and the resulting decrease in neuronal activity attenuates Mn2+ transport. The description of this critical property of Mn2+ dynamics in the brain allows a better understanding of MEMRI functional mechanisms, which will lead to more carefully designed experiments and clearer interpretation of the results.